Forms of government decentralization and institutional quality: Evidence from a large sample of nations - Rajeev K. Goel; James W. Saunoris (Asian Development Bank Institute (ADBI), 2016)
This paper studies the effects of various forms of government decentralization on institutional quality across countries. Using corruption and the shadow economy to proxy for institutional quality, as well as three forms of government decentralization (i.e., virtual, physical, and fiscal), the econometric results show virtual decentralization to be the most effective in improving institutional quality. The effects on transition and countries in Asia are also considered.
Keywords: K42; H11; H73; 330; government decentralization; shadow economy; institutional quality; virtual decentralization